AB0014 Gender-Dependent Association Between HLA-G 14B Insertion/Deletion Polymorphism and Rheumatoid Arthritis in Italian Patients. (9th June 2015) - Rubini, M.; Bonomo Roversi, E.; Aiello, V.; Khan, M.F.; Franceschelli, P.; Bassi Andreasi, R.; Farina, I.; Galuppi, E.; Govoni, M.
Abstract : Background: The human leukocyte antigen (HLA) region contributes to approximately half of the genetic susceptibility for Rheumatoid Arthritis (RA), and alleles at the HLA-DRB1 locus are associated with increased risk and more severe phenotype in RA, but this locus does not entirely explain HLA contribution to disease risk. HLA-G is a non-classical low-polymorphic HLA molecule, characterized by limited tissue distribution under normal physiological conditions. It has been shown to play a major role in immunosuppression, inhibiting the activity of cytotoxic T-lymphocytes and natural killer cells. Such feature makes HLA-G an attractive candidate gene for susceptibility to immune-mediated diseases. A 14 bp insertion/deletion polymorphism in the 3'UTR region of gene (rs16375) seems to reduce the transcript stability and associates with lower HLA-G expression. Objectives: To investigate if the rs16375 variant influences the susceptibility to develop RA using a case/control model in Italian population. Methods: We genotyped rs16375 polymorphism in a cohort of 322 Italian RA patients and in a matched group of healthy control individuals. All subject were genotyped using TaqMan technology. Results: The frequency of ins/ins genotype was significantly higher among RA patients compared to controls, indicating that ins/ins homozygotes had an increased risk to develop RA (OR=1.7 95% CI 1.2-2.6). Stratifying subjects according to gender, it came out that rs16375 genotype-associated susceptibility to RA was restricted to female patients (OR=2.4 95% CI 1.3-4.2), while rs16375 genotype had no influence on RA risk among males. Conclusions: These results suggest that HLA-G could contribute to RA pathogenesis, and that the 14b insertion/deletion polymorphism could account for gender-associated differences in genetic susceptibility to develop RA. Acknowledgements: This study was party supported by FAR grant from University of Ferrara. Disclosure of Interest: None declared